The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00408-018-0110-1
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Treatment and Outcomes for Early-Stage Non-Small Cell Lung Cancer

Abstract: Overall survival for early-stage NSCLC has significantly improved over the recent decades despite an increasing proportion of older patients and those undergoing sublobar resection or SBRT. This finding may be limited to those with adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In particular, studies continue to report significantly lower surgery rates among Blacks compared with Whites for earlystage NSCLC (1-3, 15) and worse overall survival (4). In a recent study evaluating treatment trends for early-stage lung cancer, Shin and colleagues found that over an almost 30-year time period there has been an increasing proportion of older patients and patients receiving radiotherapy alone instead of surgery; however, overall survival has improved among early-stage NSCLC and race remains a prognostic factor (16). Although the landscape for treatment for stage I NSCLC may be changing due to increased utilization of stereotactic body radiotherapy (SBRT), it remains to be seen how this impacts treatment disparities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies continue to report significantly lower surgery rates among Blacks compared with Whites for earlystage NSCLC (1-3, 15) and worse overall survival (4). In a recent study evaluating treatment trends for early-stage lung cancer, Shin and colleagues found that over an almost 30-year time period there has been an increasing proportion of older patients and patients receiving radiotherapy alone instead of surgery; however, overall survival has improved among early-stage NSCLC and race remains a prognostic factor (16). Although the landscape for treatment for stage I NSCLC may be changing due to increased utilization of stereotactic body radiotherapy (SBRT), it remains to be seen how this impacts treatment disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical lung resection (lobectomy and segmentectomy) is the mainstay treatment for early-stage non-small cell lung cancer (NSCLC) [ 1 ]. Owing to several advantages, such as less surgical trauma, a lower complication rate and improved postoperative rehabilitation, a majority of the aforementioned operations are currently performed through the video-assisted thoracic surgery (VATS) approach [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is not only the most commonly diagnosed cancer, but also the leading cause of cancer-associated death globally, with a predicted 2,28,150 novel cases and 1,47,510 deaths annually ( 1 , 2 ). Non-small cell lung cancer (NSCLC) is the most prevalent pathological subtype of lung cancer and accounts for 80–85% of all lung cancer cases ( 3 ). NSCLC is classified into lung squamous cell carcinoma, lung adenocarcinoma and large-cell lung cancer, and all three pathological classifications manifest similar biological behaviors and gene mutations ( 4 ).…”
Section: Introductionmentioning
confidence: 99%